Emotional benefit of cosmetic camouflage in the treatment of facial skin conditions: personal experience and review - Levy LL; Emer JJ (Dove Medical Press, 2012)
Lauren L Levy, Jason J EmerDepartment of Dermatology, Mount Sinai School of Medicine, New York, NY, USABackground: Recent studies highlighting the psychological benefits of medical treatment for dermatological skin conditions have demonstrated a clear role for medical therapy in psychological health. Skin conditions, particularly those that are overtly visible, such as those located on the face, neck, and hands, often have a profound effect on the daily functioning of those affected. The literature documents significant emotional benefits using medical therapy in conditions such as acne, psoriasis, vitiligo, and rosacea, but there is little evidence documenting similar results with the use of cosmetic camouflage. Here we present a review highlighting the practical use of cosmetic camouflage makeup in patients with facial skin conditions and review its implications for psychological health.Methods: A search of the Medline and Scopus databases was performed to identify articles documenting the emotional benefit of cosmetic camouflage.Results: Cosmetic camouflage provides a significant emotional benefit for patients with facial skin conditions, and this is substantiated by a literature review and personal experience. More clinical studies are needed to assess and validate the findings reported here.Conclusion: Patients with visible skin conditions have increased rates of depression, anxiety, and decreased self-esteem. It is prudent for us to consider therapies that can offer rapid and dramatic results, such as cosmetic camouflage.Keywords: facial skin conditions, psychological health, emotional benefits, cosmetic camouflage, makeup